The Moderating Role of Good Corporate Governance on the Effect of ESG Risk and Dividend Policy on Stock Prices - Taroyana, Gede Ery Patra; Atmadja, Anantawikrama Tungga; Sri Werastuti, Desak Nyoman (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the effect of ESG Risk and dividend policy on stock prices, with Good Corporate Governance (GCG) as a moderating variable. The research adopts a quantitative approach using multiple linear regression analysis and Moderated Regression Analysis (MRA). The data are obtained from the annual reports of energy sector companies listed on the Indonesia Stock Exchange (IDX). Using purposive sampling, the study yields 33 observations from 11 companies over a three-year period. The results indicate that stock price movements of energy sector companies during the 2022–2024 period are more strongly driven by financial fundamental factors, particularly dividend policy and the implementation of GCG. Meanwhile, ESG risk does not yet play a significant role in investors’ assessment of stocks. Furthermore, GCG is not proven to moderate the effect of ESG Risk or dividend policy on stock prices, suggesting that sustainability aspects and corporate governance have not been fully integrated into investment decision-making in the Indonesian capital market.